Back Cover: Characterization of the potential new phthalides in Ligusticum chuanxiong Hort. using ultra‐performance liquid chromatography coupled with quadrupole time of flight tandem mass spectrometry. Issue 10 (26th May 2017) - Zhang, Qingqing; Wang, Meiling; Wang, Qing; Zhao, Huizhen; Zhang, Zhixin; Yu, Honghong; Liu, Yuehong; Fu, Shuang; Lu, Zhiwei; Huang, Zhenghai; Xie, Ziye; Gao, Xiaoyan; et al.
Abstract : J. Sep. Sci . 2017, 40, 2123–2130 DOI:10.1002/jssc.201601443 The back cover picture shows the strategy of the identification of phthalides in Chuanxiong. The extract of Chuanxiong was detected by UPLC‐Q‐TOF/MS E and the BPI chromatogram was obtained. The phthalides were characterized comprehensively combining with the standards, in‐house database and MS fragmentation patterns. Taking the identification of senkyunolide M/Q and their isomers as an example, the process of the characterization of known phthalides and potential new ones was displayed furtherly using the above proposed method. The general structure of phthalides was summarized (bottom left) and the stereochemical structures of two phthalide monomers and one dimer were presented (top left).